Determinants of alignment level with public health risk management under COSO - ERM - Carla Janaína Ferreira Nobre Rêgo; Jeronymo José Libonati (Revista Contabilidade & Finanças)
Abstract This article aimed to analyze the determinants of alignment level of risk management practices in Brazilian municipal health management, based on the perception of municipal managers, using the Committee of Sponsoring Organizations of the Treadway Commission - Enterprise Risk Management (COSO - ERM) as a reference. This study presents theoretical and practical contributions by identifying the determinants, socioeconomic characteristics, and manager profile influencing the alignment level with municipal health risk management based on the COSO framework. In Brazilian public sector, the literature on risk management is still incipient. References are often drawn from business-oriented research, with the adoption of standards occurring coercively due to academic or private institutional pressures. The accounting literature has advanced through the proxy used to measure health risk management. Its adoption improves governance and management practices in health and education. The study used a survey based on COSO - ERM components, through the Likert scale to determine the dependent variable: the level of alignment with risk management. Additionally, a Tobit regression model with secondary variables was applied to test hypotheses regarding managers’ profiles and municipal socioeconomic characteristics. The survey results have showed that Brazilian municipalities have an 80% agreement with public health risk management practices proposed by COSO - ERM. Hypotheses related to effectiveness, 1 (health), 2 (education), and 3 (governance in information technology), were not rejected. Hypotheses 4 (indebtedness) and 5 (financial dependency) were rejected; hypothesis 6 (manager profile variables) was not rejected. This indicates that the manager’s profile is a determinant for aligning health risk management practices, while socioeconomic characteristics of indebtedness and financial dependence have a significant inverse influence.